Growth and Survival Rate of (Leptobarbus hoevenii) Using Liquid Organic Fertilizer on Culture Media - Widya Ningsih; Rusliadi Rusliadi; Iskandar Putra (Jurnal Akuakultur SEBATIN, 2024)
This research was conducted in March - May 2022 for 50 days at the Experimental Pool of the Faculty of Fisheries and Marine Affairs, Riau University, Pekanbaru. This study aims to determine the growth and survival of (Leptobarbus hoevenii) on maintenance media given liquid organic fertilizer. This study used a 100 L bucket container for as many as 15 units. The doses of Bioboost Liquid Organic Fertilizer used in this study were P0 (control), P1 (0.3 mL/L), P2 (0.4 mL/L), P3 (0.5 mL/L), P4. (0.6 /L). The method used in this study is an experimental method, namely a one-factor Completely Randomized Design (CRD) with five treatment levels and three replications. The results showed that the application of Bioboost Liquid Organic Fertilizer had a significant effect (P<0.05) on the growth and survival of jelawat fish. The best treatment in this study was P4 treatment bioboost liquid organic fertilizer at a dose of 0.6 mL/L. Water quality during the study obtained temperature (26.4-28.2 °C), pH (6.5-7.6), DO (5.6-7.4 mg/L), ammonia (0.0043-0 0.0136 mg/L), Nitrate (1.084 mg/L) and Phosphate (0.034 mg/L). Absolute weight growth (8.44 g), absolute length growth (5.51 cm), specific growth rate (2.45%), feed conversion (1.96%), and survival (100%).